Teaching Reform to the Biology Major During the COVID-19 Pandemic: A Study of the Method of Teaching Industrial Innovation and Entrepreneurial Talents - Liu, Zhe; Wang, Jingwei; Liang, Zhiming; An, Hongbo; Li, Liyang; Zang, Zhongjing; Li, Jing; Xi, Yang; Han, Tong; Liu, Shaobin; Jin, Cheng-Hao (Frontiers in Psychology, 2022)
Abstract: The biology major has developed rapidly in recent years. Biology is a science that penetrates every aspect of human life and is one of the core majors in most agricultural colleges and universities. However, many teachers lack practical experience in the subject. To overcome this problem, in recent years, we have been trying to introduce new reforms into our teaching. This article provides some insight into the way that biology majors have been reformed, which will help educators in agricultural colleges and universities. At present, teachers implement the "Industrial Innovation and Entrepreneurship Talent Cultivation" (IIETC) model, but it is not clear whether this helps biology majors to master the course and improve their practical skills. In this study, the IIETC model is outlined, and the academic achievement and satisfaction of students taught under the IIETC model are assessed. A T-test is used to examine potential differences between IIETC and traditional teaching models. In-depth interviews and questionnaires were given to two groups of students who followed different teaching models as part of an exploratory study. The aim was to explore how effective IIETC is at helping biology majors master the course and improve students' wellbeing. Our results show that compared with traditional teaching methods, the IIETC model has a significant positive impact on the academic performance and happiness of biology students. Students trained under the IIETC model were more active and scored more highly in their final exams. They were more likely to feel that they had achieved success and happiness through the course (P 0.03).